PENGARUH PENGGUNAAN MEDIA SOSIAL DAN POLA ASUH ORANG TUA DEMOKRATIS TERHADAP PRESTASI BELAJAR SISWA KELAS VI MADRASAH IBTIDAIYAH SE KOTA BATU (RETRACTED) - Mahalil asna, Megawati (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2020)
There are several causes that influence students low achievements of a learning proccess. The learning achievement can be influenved by external and internal factors. One of internal factors which influence learning achievement is the usage of social media, while external factors can be caused by the parenting. One of parenting is democratic parenting. Many parents complained and objected on the usage of social media which have a negative impact to their children, especially on their learning achievement. This research aimed to 1) analyzing the influence level of the social media usage on VI grade students of achievement of Madrasah Ibtidaiyah from Batu city. 2) analyzing the influence level of democratic parenting on VI grade students of achievement of Madrasah Ibtidaiyah from Batu city. 3) analyzing the influence level of social media usage and democratic parenting on VI grade students of achievement of Madrasah Ibtidaiyah from Batu city. The population of this research are 508 students from Madrasah Ibtidaiyah all over Batu City, by using a sample of 381 students. The instrument to collect the data is questionnaire. The result of this research are 1) there is no influence of social media usage on students learning achievements (t = 0,290; P > 0,05). Students achievement is not determined by the social media usage. The social media usage does not influence learning intensity and creativity. However, students do not use the social media to access their lesson. 2) there is no influence of democratic parenting on students learning achievement. ( t = 1,115; P > 0,05). Students achievement is not determined by democratic parenting at home. It is not the factor that determine students achievenmt level. 3) there is no positive and significant of social media usage and democratic parenting on students learning achievement (F = 0,974; P > 0,05). The social media usage and democratic parenting on students learning achievement only contribute 0,5% while 99,5% possibly influence by other factors.